Steppingstones to curriculum : A biblical path - Brummelen, Harro Van ("Colorado Springs, Colorado :" Purposeful design publications, 2002)
Includes bibliographical references and index
Includes bibliographical references p.255(-262) and index
Keywords: Education -- Curricula -- Philosophy; Education -- Aims and objectives; Teaching -- Religious aspects -- Christianity